Real time monitoring of population dynamics in concurrent bacterial growth using SIFT-MS quantification of volatile metabolites - Sovová, Kristýna; Čepl, Jaroslav; Markoš, Anton; Španěl, Patrik (The Analyst, 2013)
Population dynamics of three different bacterial species, Serratia rubidaea (R), Serratia marcescens (F) and Escherichia coli (Ec), growing in single or mixed populations in liquid media, was monitored by real time headspace quantification of volatile compounds using selected ion flow tube mass spectrometry, SIFT-MS. The three bacterial species interact with each other in a competitive fashion in a way similar to the game "rock-paper-scissors" (R-Ec-F). The concentrations of volatile metabolites (ammonia, ethanol, acetaldehyde, propanol, acetoin, acetone and acetic acid) were measured in the headspace of the individual species and of their mixtures continuously for 24 hour periods. The results demonstrate that dynamics in bacterial cultures can be monitored using SIFT-MS in real time.
Keywords: časové faktory; Escherichia coli; Serratia marcescens; těkavé organické sloučeniny; hmotnostní spektrometrie; Time Factors; Volatile Organic Compounds; Mass Spectrometry